Wiskott‐Aldrich Syndrome Caused by a New Mutation Associated with Multifocal Dermal Juvenile Xanthogranulomas. Issue 5 (12th November 2012) - Jesenak, Milos; Plamenova, Ivana; Plank, Lukas; Banovcin, Peter
Abstract Wiskott‐Aldrich syndrome is a rare X‐linked primary immunodeficiency clinically characterized by the triad of microthrombocytopenia, immunodeficiency, and eczema. Juvenile xanthogranuloma is a well‐recognized benign disorder of infancy and early childhood from the group of non‐Langerhans cell histiocytoses, with a good prognosis and spontaneous involution. We report a boy with Wiskott‐Aldrich syndrome caused by a new, not previously described mutation associated with multifocal juvenile xanthogranuloma.